Discovery of 1H-pyrazolo[3, 4-b]pyridines as potent dual orexin receptor antagonists (DORAs). Issue 23 (1st December 2015) - Behnke, Dirk; Cotesta, Simona; Hintermann, Samuel; Fendt, Markus; Gee, Christine E.; Jacobson, Laura H.; Laue, Grit; Meyer, Arndt; Wagner, Trixie; Badiger, Sangamesh; Chaudhari, Vinod; Chebrolu, Murali; et al.
Graphical abstract: Abstract: Compound rac -1 was identified by high throughput screening. Here we report SAR studies and MedChem optimization towards the highly potent dual orexin receptor antagonists ( S )-2 and ( S )-3 . Furthermore, strategies to overcome the suboptimal physicochemical properties are highlighted and the pharmacokinetic profiles of representative compounds is presented.